Acuña, J. K., Sánchez, E. and Garza, M. Cartographies of the pandemic in times of civilizing crisis. Approaches to its understanding from Mexico and Latin America. Mexico City: Editions the Library, 280 pp. - Velázquez Aguilar, Alberto (Revista revoluciones, 2021)
This book, coordinated by the aforementioned authors, offers an excellent analysis of the effects of the pandemic in Latin American countries such as Brazil, Argentina, Chile, Peru, and Mexico. This work is divided into three sections: The State and the accumulation due to the pandemic, The reorganization of immediate life during the pandemic, and Resistance and sociocultural contradictions. Under these work routes we can observe a detailed investigative analysis of the coronavirus, perhaps currently considered the mother of all crises that humanity has known. The times of pandemic in Latin America have been considered chaotic and thought of as a health war against an invisible army; We are talking about a simple metaphor in front of a dramatic scene with a gloomy horizon. This leads us to generate a reinforcement of social control and health security where the change of what we knew as daily life from this health war would be about to change completely and would lead us to the urgency of preparing ourselves to face in the best way possible or reorganize our social, political, economic and educational activities. With all of them, the sanitary distancing established by each of the governments arises as a preventive measure against possible contagion, which leads us to one more crossroads, we talk about that this isolation allows us to prioritize the survival of the largest possible number of lives, but it leads us to the almost total brake on the economy of Latin American countries generated by the pandemic.